Interbank Market Integration under Asymmetric Information - Freixas, Xavier; Holthausen, Cornelia (Review of Financial Studies, 2005)
Cross-country bank lending appears to be subject to market imperfections leading to persistent interest rate differentials. In a model where banks need to cope with liquidity shocks by borrowing or by liquidating assets, we study the scope for international interbank market integration with unsecured lending when cross-country information is noisy. We find that an equilibrium with integrated markets need not always exist, and that it may coexist with one characterized by segmentation. A repo market reduces interest rate spreads and improves upon the segmentation equilibrium. However, it may destroy the unsecured integrated equilibrium.